Exploring the competencies of operating room nurses in mobile surgical teams based on the Onion Model: a qualitative study - Aifang Niu; Huijuan Ma; Zhe Chen; Xiaoli Zhu; Yu Luo (BMC, 2023)
Abstract Background With the frequent occurrence of public health emergencies, conflicts and natural disasters around the world, mobile surgical teams are becoming more crucial. The competency of the operating room (OR) nurse has a substantial impact on the effectiveness and quality of the surgical team's treatment, still there is limited knowledge about OR nurse competencies in mobile surgical teams. This study aimed to explore the competencies of OR nurses in mobile surgical teams based on the Onion Model. Methods We conducted a qualitative descriptive study of participants from 10 mobile surgical teams in 2022. Twenty-one surgical team members were interviewed, including 15 OR nurses, four surgeons, and two anesthesiologists. Data were collected through semi-structured interviews. The data were analyzed using Mayring's content analysis. Results Twenty-eight competencies were found in the data analysis, which were grouped into four major domains using the Onion Model. From the outer layer to the inner layer were knowledge and skills, professional abilities, professional quality, and personal traits. The qualitative data revealed several novel competencies, including triage knowledge, self and mutual medical aid, outdoor survival skills, and sense of discipline. Conclusions The application of the Onion Model promotes the understanding of competency and strengthens the theoretical foundations of this study. New competencies can enrich the content of the competencies of OR nurses. The results of this study can be used for clinical recruitment, evaluation and training of OR nurses in mobile surgical teams. This study encourages further research to develop competency assessment tools and training programs for OR nurses.